Respons Pertumbuhan Kedelai (Glycine max L. Merr.) terhadap Seed Treatment Matriconditioning dan Aplikasi Pemupukan yang Berbeda: Response of Soybean Growth (Glycine max L. Merr.) Under Seed Treatment Matriconditioning and Different Fertilizing Applications - Ari Wahyuni; Nurman Abdul Hakim; Ria Putri; Tera Feronica (Politeknik Negeri Lampung, 2022)
One of the essential factors in crop production is the use of quality seeds. The availability of quality seeds affects the quality and yield. Currently, in the field is that soybean seeds sold by seed stores are seeds that have deteriorated and are stored in unfavorable conditions, causing the quality of the seeds to decline. To continue planting, a technique for improving the performance of soybean seeds is required through matrix conditioning and fertilization. This study aimed to determine the effect of matrix conditioning and fertilization treatment on increasing the growth of soybean seeds stored for two months. This study used a two-factor completely randomized design (CRD) with three replications. The first factor was matrix conditioning media (without matrix conditioning, sawdust, and husk charcoal). The second factor was fertilization (without organic fertilizers and inorganic fertilizers), 100% organic fertilizers, 100% inorganic fertilizers, and 100% organic fertilizers + 50% inorganic fertilizers). The data were tested by using 5% BNT. Variables observed were plant height, number of leaves, leaf dry weight, stem dry weight, root dry weight, and number of root nodules. The results showed that there was an interaction effect between matrix conditioning and fertilization media on the observed variables of plant height, leaf dry weight, and single matrix conditioning treatment that affected the observed variables of root dry weight and number of root nodules in improving seed quality and growth. Keywords: soybean, quality, matrixconditioning, fertilization